2009
DOI: 10.5216/ree.v10i2.8040
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida de portadores de dores crônicas em tratamento com acupuntura

Abstract: Dor é sintoma de alerta, comum nas enfermidades e com impacto negativo na vida das pessoas, que buscam alternativas para seu alívio, sendo a acupuntura usada pelo efeito analgésico. Questiona-se se a qualidade de suas vidas (QV) foi alterada após o início da acupuntura. Objetivou-se analisar a QV dos portadores de dor crônica que utilizam acupuntura. Estudo descritivo-analítico realizado em uma clínica de acupuntura em Goiânia -GO, entre janeiro e fevereiro de 2006. Dados foram coletados utilizando o SF-36, ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
4
0
14

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 5 publications
(12 reference statements)
4
4
0
14
Order By: Relevance
“…These data confirm the findings of a study conducted by other researchers with individuals who presented the same domains, in the same order of compromise [22, 23]. When individuals are affected by chronic disease, it is not only the pathologic factor that influences the situation, because there are changes in their lives related to physical discomfort, losses of a personal, financial and social order [22]. It has been shown that the repercussion of chronic pain on the QoL is more related to neuropathic pain than to intensity or duration [20].…”
Section: Discussionsupporting
confidence: 91%
“…These data confirm the findings of a study conducted by other researchers with individuals who presented the same domains, in the same order of compromise [22, 23]. When individuals are affected by chronic disease, it is not only the pathologic factor that influences the situation, because there are changes in their lives related to physical discomfort, losses of a personal, financial and social order [22]. It has been shown that the repercussion of chronic pain on the QoL is more related to neuropathic pain than to intensity or duration [20].…”
Section: Discussionsupporting
confidence: 91%
“…The aims we initially proposed in the PROSPERO protocol for this systematic review included examining whether religion is associated with measures of pain and function and the extent to which pain-related beliefs, pain-coping responses and catastrophizing in adults with chronic pain are different or similar in people with different religious affiliations. The four studies (Basinski et al 2013;Brasil et al 2008;Offenbaecher et al 2017;Parenteau et al 2011) examining such comparisons were not included in this review, and analyses and results related with these comparisons, were omitted from this review due to ethical concerns, as previously noted. Thus, 20 studies were included in the final analysis of the systematic review.…”
Section: Study Selectionmentioning
confidence: 99%
“…The population evaluated presented moderate pain (5.6 ± 0.47) and interference both with functional and emotional activities (3.48 ± 0.21 and 3.64 ± 0.18, respectively). A study 21 on the impact of chronic pain on quality of life has shown that it has a negative impact on quality of life of up to two thirds of patients, especially on the ability to exercise, to practice sports, to perform daily life activities, as well as to perform labor activities. A different study 22 evaluating functional capacity by the Older American Resources and Services (OARS) scale, validated for the Portuguese language, with 111 elderly people with chronic pain and living in the area of a BHU in the city of Londrina, PR, has observed interference, especially with sleep, mood and leisure, that is, chronic pain has negative impact on patients' functional capacity, especially to perform daily activities, and may limit or even lead to functional incapacity.…”
Section: Discussionmentioning
confidence: 99%